Tipificação de isolados deCurtobacterium flaccumfaciens pv. flaccumfaciens por bacteriocinas - Maringoni, Antonio Carlos [UNESP]; Kurozawa, Chukichi [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2002)
Este trabalho objetivou avaliar a produção e a sensibilidade à bacteriocinas, de 17 isolados de Curtobacterium flaccumfaciens pv. flaccumfaciens. Doze isolados foram procedentes do Estado de São Paulo e cinco de coleções internacionais. Apenas nove isolados de C. flaccumfaciens pv. flaccumfaciens foram bacteriocinogênicos, e os 17 isolados avaliados foram separados em 12 grupos, conforme a sensibilidade às bacteriocinas produzidas pelos isolados bacteriocinogênicos.

The objective of this work was to evaluate the production and sensitivity of seventeen isolates of Curtobacterium flaccumfaciens pv. flaccumfaciens to the bacteriocin. Twelve isolates were collected in the State of São Paulo, Brazil, and five were originated from international collection. Only nine isolates of C. flaccumfaciens pv. flaccumfaciens were bacteriocinogenic and the seventeen isolates analyzed have been separated in twelve groups according to the sensitivity to bacteriocins produced by bacteriocinogenic isolates.
Curtobacterium flaccumfaciens pv. flaccumfaciens typification by bacteriocin
Keywords: Phaseolus vulgaris; bactéria; cultura microbiana; bactericida; Phaseolus vulgaris; bacteria; microbial culture; bactericides